The Effect of Audit Fees and Audit Committee Independence on Audit Quality (Case Study of Infrastructure Companies in the Telecomunication Sub-Sector Listed on the Indonesia Stock Exchange for the years 2017-2021) - Zulfaa Boedhiarti Azan; Neni Maryani (Lafadz Jaya Publisher, 2023)
This study aims to examine the influence of Audit Fees and Audit Committee Independence on Audit Quality in the telecommunications infrastructure companies during the period of 2017-2021. The population in this study consists of telecommunications infrastructure companies. This study is quantitative research. The data used in this study was obtained from the website www.idx.co.id and the annual reports that have been audited for each respective year, available on the official websites of the respective companies. The data collection technique used in this study employed purposive sampling, and a total of 35 data samples were obtained during the observation period. The sample data was analyzed using SPSS version 22 for Windows. The results of the study indicate that partially, audit fees do not have a significant effect on audit quality, and audit committee independence does not have a significant effect on audit quality. Simultaneously, audit fees and audit committee independence have an effect on audit quality.